Hyperhomocysteinemia and lipid peroxidation in stable coronary heart disease - O. L. Belaya; N. V. Fedorova; I. G. Fomina (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To compare homocysteine, lipids, and lipid peroxidation (LP) products’ levels in plasma of coronary heart disease (CHD) patients with stable angina and dyslipidemia, and relatively healthy individuals. Material and methods. The study included 30 CHD patients (Functional Class, FC, II-III angina) and 15 relatively healthy volunteers. Plasma levels of lipids, LP products (malone dialdehyde, MDA), homocysteine (by highly effective liquid chromatography method), as well as coagulation and fibrinolysis parameters were measured. Results. In 86,7% of CHD patients with II-III FC angina, homocysteine and MDA levels were significantly higher than in healthy controls, and in 30% these levels were higher than standard norm. Plasma homocysteine levels correlated with LP activity in CHD patients (r=0,59). Methionine load test helped to diagnose latent hyperhomocysteinemia. Conclusion. CHD patients with II-III FC angina, hypercholesterolemia and hyperlipoperoxidemia had significantly higher homocysteine levels, compared to relatively healthy individuals (р<0,001).